(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
The available studies have shown that Gynmnarchus niloticus, Cuvier (1829) in Nigerian freshwater bodies record low parasitic infections. Therefore, both parasitic and histopathological studies on the liver of G. niloticus, Cuvier (1829) as one of the most commonly occurring species were carried out to determine the healthy state of these species in the Anambra River after initial observation in one G. niloticus sample from Imo River in 2017. Though no protozoan or helminth infection was detected, there was liver infection by an opportunistic pathogen - Aeromonas sp. 115 samples of G. niloticus were collected and examined for the presence of a pathogen from January to June 2023, 32 (27.8 %) were infected by Aeromonas sp.Â All the affected G. niloticus were asymptomatic. Sections of the liver showed severe, multifocal, degeneration and necrosis of the hepatocytes with varying degrees of leucocytic/inflammatory cell infiltration.Â The degenerate hepatocytes showed multiple clear vacuoles in their cytoplasm (micro-vesicular lipidosis). Within the necrotic areas, bacterial colonies consisting of slender short to medium-sized filamentous rods were observed.Â Clear large vacuoles of varying sizes in the tissue (likely gas bubbles as a result of gas-forming bacterial activity) were also observed.Â Also, soil nematodes from the soil around the water body were analyzed for heavy metals contents using atomic absorption spectrometry (AAS) mg/kg as a possible source of stress to G. niloticus involving eight elements but three namely Cd (0.005Â±0.001) mg/kg, Cr (0.0095Â±0.0015) mg/kg, Pd(0.008Â±0.000) mg/kg were detected in low, safe levels.